Effects of trampling on a terrestrial orchid environment - Light, Marilyn (Universidad de Costa Rica, 2015)
Orchids and soil communities that support them may be affected when we monitor or conduct inves- tigative procedures, or through tourism especially during the blooming season, but this has never been investigated or quantified (Light 2004). The immedi- ate and direct effect of human disturbance including crushing of flowering plants and seedlings is obvious: broken stems are unlikely to resume growth and a season’s reproductive effort can be lost.